“Implementación de un sistema de gestión de la información de proyectos de investigación de cada una de las carreras de la Universidad Técnica de Cotopaxi Extensión La Maná aplicando la metodología de desarrollo de Software Scrum.” - Mendoza Franco, Diana De Jesús (2022)
The present investigation titled as: Feasibility study for the production and commercialization of red The Extension of the Technical University of Cotopaxi at La Maná includes business administration, accounting and auditing, electromechanics, information systems, agronomy, agribusiness, and tourism careers where teachers carry out research projects in each cycle with the support of a teacher in charge and assistant professors as mediators, students can also participate on it as well as others. With the previously mentioned research projects, it is highly likely to generate scientific articles during the execution time, which are usually published in indexed journals whose authorship belongs to students and teachers of the UTC extension La Maná. It is significant to mention that the main problem points out to the traditional methods employed in the processes as physical files that cause documents' accumulation. Subsequently, the implementation of an information management system for research projects directed to the university careers would facilitate the processes involved in research works since having digitized information will be essential to generate indicators or metrics to represent within a Dashboard through decision-making that can improve the research operations in the institution. In the same way, for the proposal advance, developmental tools will be used such as a PHP v7 programming language, MariaDB database, Bootstrap framework, and an Agile Scrum development methodology. Moreover, research techniques such as field observation, interviews, and surveys were useful to verify the needs and carry out a survey of software requirements. As a result, a management information system was obtained to control the fulfillment of research projects exhaustively according to the user requirements and perspectives. In such a way, information management systems help to have a detailed follow-up of the activities executed by the people in charge of developing a research project.